Two Sides of Social Media: an Assistance on Youth Using Social Media In Tuban District - Hidayati, Niswatin Nurul (TAAWUN, 2024)
The aim of the assistance was to explore the multifaceted role of assistance programs dedicated to guiding and supporting youth in their use of social media in Tuban District, especially in Montong Sub District. As adolescents and young adults increasingly turn to online platforms for communication, information sharing, and identity formation, the need for constructive guidance becomes paramount. Recognizing the transformative potential of social media in the lives of the youth, this article aims to shed light on initiatives aimed at providing assistance and mentorship. The mentoring method used was in the form of seminars and practical sessions. Based on the mentoring program conducted for the youth in the Montong Sub District Tuban District, it can be concluded that internet usage has been massively adopted by the youth. However, this usage is not yet fully harnessed for the benefit of both individuals and institutions in their respective workplaces. Additionally, it can be said that through this seminar, the youth gained insights into various aspects, ranging from utilizing social media for branding to obtaining more information about the internet and its economic impact, the positive and negative aspects of social media, and social media ethics. A suggestion from the author is the hope that similar activities can continue to be implemented continuously. Furthermore, it is advisable to incorporate more in-depth digital literacy aspects in subsequent activities